COMPOSITION OF RESULTS AND CATCH RATE OF SURFACE GILLNETS AT COASTAL FISHERY PORT CAROCOK TARUSAN - Andhini, Jessyca; Nurhayati; Ramdhani, Farhan; Nelwida; Rahayu, Dyah Muji; Gelis, Ester Restiana Endang (Jurnal Penelitian Perikanan Laut (Albacore), 2025)
The catch is influenced by the ability of the fishing gear to obtain organisms in a certain period of time called the catch rate. Until now it is not known how effective the performance of the surface gill net fishing gear is. This study aims to determine the composition of the catch, catch rate, frequency of occurrence of fish species and factors that affect the catch in the surface gill net. The method used is the survey method with data collection using purposive sampling. The results of the study showed that the total catch was 2.207 fish weighing 644,706 kg, which was divided into two, namely the main catch (HTU) with a weight percentage of 74,73% and bycatch (HTS) with a percentage of 25,27%. The percentage of catch in units of fish, in HTU of 89,76% and HTS of 10,24%. It was concluded that the composition of the surface gill net catch has 13 species, the highest catch rate and frequency of occurrence is mackerel (Rastrelliger sp.) as much as 2,61 kg/hour with 86,67% frequency of occurrence. The factor that significantly influences the catch with an increasing trendline is the duration of operation with a P-value of 0,0007. Key words: catch rate, frequency of occurrence, rastrelliger, surface gill net, yield composition